How Does Pacific Decadal Oscillation Modulate Extreme Heavy Rainfall Frequency Over Far East Asia? - Haerin Park; Taeho Mun; Dong‐Hyun Cha; Myong‐In Lee; Minkyu Lee; Seung‐Ki Min; Baek‐Min Kim; Seok‐Woo Son (Geophysical Research Letters)
Abstract We investigated the relationship between heavy rainfall events (HREs) and the Pacific Decadal Oscillation (PDO) occurring in Korea over Far East Asia for 40 years (1981–2020). Using K‐means clustering on the low‐level jet, we identified four clusters (C1–C4), with C1 being characterized by weaker synoptic conditions. Out of the four clusters, C1 represented localized extreme HREs compared with the other clusters. Interestingly, only the HRE frequency of C1 was found to have a strong negative correlation with PDO. During the negative‐PDO, sea surface temperature increased above 30°N, which decreased the meridional temperature gradient. This weakened the atmospheric circulation and created thermodynamic instability (i.e., weakened upper jet, increased low‐level temperature, higher atmospheric water capacity), creating a favorable environment for HRE in C1. However, this negative‐PDO environment provided somewhat unfavorable conditions for other clusters (C2–C4), so the PDO impact was insignificant.